SAT0398 Diagnostic value of anti mutated citrullinated vimentin in comparison to anti-cyclic citrullinated peptide and anti-viral citrullinated peptide 2 antibodies in rheumatoid arthritis: A multicentric study by firma group. (23rd January 2014) - Bartoloni, E.; Alunno, A.; Bistoni, O.; Bizzaro, N.; Morozzi, G.; Doria, A.; Mathieu, A.; Lotzniker, M.; Allegri, F.; Riccieri, V.; Alpini, C.; Gabrielli, A.; et al.
Abstract : Background: In recent years the diagnostic approach to rheumatoid arthritis (RA) significantly changed. Among new serological assays, an ELISA test detecting antibodies directed against recombinant mutated citrullinated vimentin (anti-MCV), a protein widely expressed in the synovium, has been introduced to improve diagnosis. Anti-MCV appear slightly more or as sensitive as anti-cyclic citrullinated protein antibodies (anti-CCP), but less specific. However, its additional diagnostic value with respect to anti-CCP both in early and established RA is controversial. Objectives: Evaluate the diagnostic performance of anti-MCV assay in RA and to compare it to a standard anti-CCP test and the recently developed assay targeting viral citrullinated peptide 2 (VCP2) (1, 2) in a large cohort of RA patients and healthy and disease controls. Methods: Sera (n=512) from long-standing RA patients (n=285) and healthy and disease controls (n=227) were randomly collected. Anti-CCP were measured by the routine method used in each Center. As 4 different assays were used, anti-CCP values were normalized and expressed as a ratio. Anti-VCP IgG were detected by the 2nd generation method (Astra Diagnostici, Milan, Italy) and anti-MCV by the available ELISA kit (Orgentec Diagnostika GmbH, Mainz, Germany). The receiver-operating characteristic (ROC) curve was calculated to determine the optimal cutoff values for each antibody assay. Results: At the calculated cutoff value of 55 U/mL, anti-MCV resulted to have a sensitivity of 59% and a specificity of 92%. In comparison, anti-CCP (calculated cutoff of 5 U/mL) and anti-VCP2 (calculated cutoff of 21 AU) displayed a sensitivity of 77% and 61% and a specificity of 96% and 95%, respectively. Of interest, a high percentage of healthy subjects as well as Epstain Barr and hepatitis C virus-infected patients resulted anti-MCV positive at the manufacturer recommended cutoff value of 20 U/mL. Conclusions: In our large cohort of RA patients, at the calculated cutoff of 55 U/mL, anti-MCV demonstrated lower sensitivity than anti-CCP and VCP2 test, thus not allowing to confirm previously published data. Moreover, the high rate of detection in infectious diseases limits its diagnostic value in undifferentiated arthritis. On the basis of our results, an international validated anti-MCV cutoff value to standardize the results is surely needed. References: Bizzaro N et al., J Clin Pathol 2011;64:1139 Pratesi F et al., Clin Exp Immunol 2011;164:337 Disclosure of Interest: None Declared